Het revisionisme in de sociaaldemokratie : rede, Amsterdam, 4 april 1909. - Bernstein, Eduard; Vliegen, Wilhelmus Hubertus (Willem) (Amsterdam : Cohen, 1909)
Bibliotheek E. Anseele
Nederlands
Brochure